Empowerment of MSMEs to Increasing Competence in Public Communication - Iis Elfa Syafmaini; Jaenal Mutakin; Ace Suryadi; Asep Saepudin; Zulharman Zulharman; Makan Sacko (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
The objectives of this study are 1) to analyze the implementation of public speaking training to improve the digital communication competence of Micro-, Small and Medium-sized Enterprises (MSMEs) entrepreneurs in Cibeurum Village, Cimahi City, 2) to identify public speaking training strategies to enhance digital communication competence for MSMEs entrepreneurs, 3) to evaluate the responses to the public speaking training. This study applied qualitative methods with descriptive methods. Data collection techniques used two data sources, primary and secondary sources. The processes for collecting data were through observation, interviews, and documentation studies. The results and discussion of this research is training public speaking as an effort to increase the competence of MSME actors has proven to have a positive impact on increasing the self-skills and confidence of MSME actors in developing their business.